The Rep78 gene product of adeno-associated virus (AAV) self-associates to form a hexameric complex in the presence of AAV ori sequences. - Smith, R H (1997)
The Rep78 and Rep68 proteins of adeno-associated virus (AAV) are replication initiator proteins that bind the viral replicative-form origin of replication, nick the origin in a site- and strand-specific fashion, and mediate vectorial unwinding of the DNA duplex via an ATP-dependent helicase activity, thus initiating a strand displacement mechanism of viral DNA replication. Genetic and biochemical studies have identified Rep mutants that demonstrate a trans-dominant negative phenotype in vitro and in vivo, suggesting the possibility that multimerization of Rep is essential for certain replicative functions. In this study, we have investigated the ability of the largest of the Rep proteins, Rep78, to self-associate in vitro and in vivo. Self-association of Rep78 in vivo was demonstrated through the use of a mammalian two-hybrid system. Rep-Rep protein interaction was confirmed in vitro through coimmunoprecipitation experiments with a bacterially expressed maltose-binding protein-Rep78 fusion protein in combination with [35S]methionine-labeled Rep78 synthesized in a coupled in vitro transcription-translation system. Mapping studies with N- and C-terminal truncation mutant forms of Rep indicate that amino acid sequences required for maximal self-association occur between residues 164 and 484. Site-directed mutagenesis identified two essential motifs within this 321-amino-acid region: (i) a putative alpha-helix bearing a 3,4-hydrophobic heptad repeat reminiscent of those found in coiled-coil domains and (ii) a previously recognized nucleoside triphosphate-binding motif. Deletion of either of these regions from the full-length polypeptide resulted in severe impairment of Rep-Rep interaction. In addition, gel filtration chromatography and protein cross-linking experiments indicated that Rep78 forms a hexameric complex in the presence of AAV ori sequences.